Practical Approaches for Providing Empirical Data on Seabird Behavior and Prey Assemblages in Tidal Channels - Fraser, Shaun; Waggitt, James J. (Frontiers in Marine Science, 2022)
Persisting knowledge gaps relating to the ecological context and potential environmental impacts of marine renewable energy (MRE) devices continue to add substantial costs and uncertainty to MRE projects globally. Increasingly sophisticated technological approaches to environmental monitoring can have fundamental non-trivial shortcomings for environmental impact assessment (EIA), whilst substantial practical and financial costs of deployments can prevent their application. For the tidal stream energy (TSE) sector, there is a need for practical and cost-effective methods that can provide site-specific information on predator behavior and associated prey assemblages. Considering existing knowledge of animal communities in tidal channel environments, a proportional approach using shore-based observation and baited fish trap methods was developed. During April 2021, a trial of these methods was conducted in tidal channel environments in Shetland, UK. The practical application of the proposed approach is demonstrated here with results from three tidal channels including Bluemull Sound, the site of active TSE installations (the Shetland Tidal Array). Observation of predator behavior across the study sites are reported for great cormorant Phalacrocorax carbo and European shag Phalacrocorax aristotelis. Seabird diving data calculated from the shore-based observations provided metrics relevant to informing EIA and collision risk modelling including dive duration, dives per minute, and % time underwater. Fish trap deployments targeted the benthic and demersal prey of these predators in the three study sites and across a range of depths and hydrodynamic conditions. A variety of fish and invertebrate species known to be important components of benthic-foraging seabird diet were successfully captured by the traps, providing basic biological information on the prey assemblages observed in each site. The fish species observed in the highest abundance were saithe Pollachius virens and cod Gadus morhua. Benefits, limitations, and applications of this approach are discussed along with various factors relating to the performance of both methods. The shore-based observations rapidly identified relevant patterns in predator foraging activity which informed the targeted deployment of fish traps to provide complementary prey data. This novel combined approach has potential to reduce costs and uncertainty in EIA and for supporting the responsible development of the MRE industry.